2014
DOI: 10.1021/jm500496m
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 1-Butyl-3-chloro-4-(4-phenyl-1-piperidinyl)-(1H)-pyridone (JNJ-40411813): A Novel Positive Allosteric Modulator of the Metabotropic Glutamate 2 Receptor

Abstract: We previously reported the discovery of 4-aryl-substituted pyridones with mGlu2 PAM activity starting from the HTS hit 5. In this article, we describe a different exploration from 5 that led to the discovery of a novel subseries of phenylpiperidine-substituted pyridones. The optimization strategy involved the introduction of different spacers between the pyridone core and the phenyl ring of 5. The fine tuning of metabolism and hERG followed by differentiation of advanced leads that were identified on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…281 Although efficacy signals were met on some measures, the signal on the primary outcome measure was not significant, and the overall data did not support continued development of the compound in anxious depression. 278 …”
Section: 2 Allosteric Modulators Of the Mglu2 And Mglu3 Receptorsmentioning
confidence: 99%
“…281 Although efficacy signals were met on some measures, the signal on the primary outcome measure was not significant, and the overall data did not support continued development of the compound in anxious depression. 278 …”
Section: 2 Allosteric Modulators Of the Mglu2 And Mglu3 Receptorsmentioning
confidence: 99%
“…Reference PAMs in the field include JNJ-40068782 [21], BINA [22] and JNJ-46281222 [23]. Two PAMs entered clinical trials, AZD8529 of AstraZeneca and JNJ-40411813 (also known as ADX71149) from Janssen/Addex [24][25][26][27][28][29]. A number of mGlu 2 negative allosteric modulators (NAMs) have been characterized in vivo, including a recent series of NAMs from Janssen and RO4491533 and decoglurant from Roche, of which the latter also advanced into clinical trials [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…JNJ‐40411813 (also known as ADX71149) from Janssen Pharmaceuticals and Addex Therapeutics failed to meet the criterion for efficacy signal in patients with major depressive disorder with significant anxiety symptoms. In contrast, in an exploratory phase 2a study in schizophrenia, not powered to determine statistical significance of effects rather a signal generation study, JNJ‐40411813 met the primary objectives of safety and tolerability and also demonstrated an effect in patients with residual negative symptoms (Cid et al , ).…”
Section: Introductionmentioning
confidence: 99%